Kajian Tanda dan Simulasi pada Game Nusantara Online - Rahina Nugrahani; Yasraf Amir Piliang (Wimba : Jurnal Komunikasi Visual, 2010)
Game as a cultural interactive product can be understood by its idea in producing message. Nusantara Online is one of MMORPG (Massively Multiplayer Online Role Playing Game) developed by Indonesian game developer. As a game with historical theme, there are some efforts to reconstruct the classical Majapahit social life. Through virtual comodity offered by game, the value and naration of the history potentially change.This research is aimed to analyse the signs that build a system presenting reality and simulation in the game. In the context of hypersemiotics, the fussion of reality and non reality is a result of sign using that creates hypereality (hypersigns). Identification of hypersigns explained in simulation frame of character, environment, space and time. Some aspects related to the background of simulation explained in logic of simulation.As the result of this research found the signs that construct visual element of this game are a system that makes player exist in a virtual world of Majapahit. History aspect has been through a framing process that makes some events in Majapahit history no longer being dominant in this game. In the other hand, historical aspect seems dominant in the using of Majapahit figure's name, some visual elements and some things related to legend and myth. History in Nusantara Online game is an artificial history, its naration depends on the player's choice in experiencing every details of the game. Simulations in the elements of character, environment, space and time are related to contemporary aspect and postmodernism culture where the players live in.